2020
DOI: 10.1097/md.0000000000020045
|View full text |Cite
|
Sign up to set email alerts
|

Disruption within brain default mode network in postpartum women without depression

Abstract: Previous studies have demonstrated that cognitive dysfunction is associated with neurophysiological changes in postpartum period. This study aimed to investigate the intrinsic functional connectivity (FC) pattern within the default mode network (DMN) and its associations with cognitive dysfunction in postpartum women without depression revealed by resting-state functional magnetic resonance imaging (fMRI). Resting-state fMRI scans were acquired from 21 postpartum women and 21 age- and education-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Alterations in endogenous sex steroid hormone levels during the postpartum period may result in widespread neural changes, including in the PCC ( Fisher et al, 2016 ). Furthermore, our previous study had mainly demonstrated decreased resting-state FC patterns within the DMN regions, especially the PCC, which were associated with impaired cognitive function in primiparous women without depression ( Zheng et al, 2020 ). Therefore, our findings indicate that reduced PCC connectivity pattern within the DMN may be responsible for the impaired short-term memory in parous women, which is different from that in primiparous women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alterations in endogenous sex steroid hormone levels during the postpartum period may result in widespread neural changes, including in the PCC ( Fisher et al, 2016 ). Furthermore, our previous study had mainly demonstrated decreased resting-state FC patterns within the DMN regions, especially the PCC, which were associated with impaired cognitive function in primiparous women without depression ( Zheng et al, 2020 ). Therefore, our findings indicate that reduced PCC connectivity pattern within the DMN may be responsible for the impaired short-term memory in parous women, which is different from that in primiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Our combined ALFF and ReHo analyses revealed reduced neuronal activity, mainly in the PCC and prefrontal cortex, which was associated with executive dysfunction in primiparous women ( Zheng et al, 2018 ). Furthermore, compared with the nulliparous women, postpartum women had a significantly decreased FC between the PCC and the left mPFC ( Zheng et al, 2020 ). The current study extends the work that aberrant brain connectivity in the prefrontal cortex may play a pivotal role in postpartum cognitive impairment, especially the executive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in resting-state brain function associated with motherhood may uncover global, generalised changes in brain function, with broader impacts for maternal behaviour, beyond responses to infant stimuli. A small number of seed-based resting-state connectivity studies have measured connectivity in a priori defined networks, and these studies have shown differences between mothers and non-mothers in six key regions of the putative parental caregiving network: the dorsomedial prefrontal cortex, ventromedial prefrontal cortex, parahippocampal gyrus, posterior cingulate cortex, amygdala, and nucleus accumbens 3,18,22,24,[28][29][30] (Figure 1a). Resting-state functional connectivity between the amygdala, nucleus accumbens, and dorsomedial prefrontal cortex are related to positive maternal care.…”
mentioning
confidence: 99%